Detection of inducible clindamycin resistance (MLSBi) among methicillin-resistant Staphylococcus aureus (MRSA) isolated from health care providers - Navidinia, Masoumeh (Archives of Advances in Biosciences, 2015)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most important agents producing nosocomial diseases in hospitalized children. Then, screening of health care providers who are in direct contact with patients in hospital is necessary. The objective of this study was to investigate MRSA collected isolates for MLSB phenotypes, in particular inducible clindamycin resistance (MLSBi).Two hundred and twenty nine health care providers were examined and nasal samples for S. aureus culture and sociodemographic data were obtained from them during one year august 2012 - july 2013. After MRSA identification, all isolates were examined for antibiotic resistant pattern.Staphylococci were isolated from 27 samples. Twenty one of them were MRSA. All isolates sensitive to linezolid and vancomycin. D-tests identified 6 isolates (28.6%) with inducible resistance to clindamycin (MLSBi phenotype). Carrier samples screening are considered less than clinical samples. Treatment of variety of infectious diseases due to resistant bacteria is difficult. So, annual screening of these individuals, detecting the carriers and decolonizing them to reduce transmission of S. aureus in the hospital is necessary.